China’s Re-Construction of Old Silk Road and Its Implications on Indonesia - Hara, Abubakar Eby; Agung, Cipto Rizqi; Trihartono, Agus (Journal of Integrative International Relations, 2019)
This paper tries to trace how China revived the Ancient Silk Road and how it has redefined relations with other countries in the world, including Indonesia. Under President Xi Jinping, China revived the concept of the Silk Road through the Belt and Road Initiative (BRI) policy. BRI has two main parts, the land silk route known as the Silk Road Economic Belt and the sea route known as the Maritime Silk Road. The revival of the silk route has its charm so that many countries, including Indonesia, welcome BRI's presence. But before Indonesia gets involved further in the BRI, it is crucial for Indonesia to examine the extent to which the ideologies and values carried out in the reconstruction of the BRI concept threatens or benefits Indonesia's interests. Through a study of the discourse and views of Chinese leaders, this paper will explore how the traditional values of the silk road are modified to conform to the values of modern cooperation and trade to suit China ambition to be a great power.